Balanced scorecard como framework para as atividades de auditoria operacional em instituições federais de ensino superior - Lima, Giovana Daniela de (2018)
The fulfillment of the public function commands the manager to adapt the resources administrated by him in the name of society. Therefore, it's required the application of control mechanisms to ensure that the public resources are employed on behalf of the citizens. In Brasil the Instituições Federais de Ensino Superior (IFES) [Federal Institute of higher education] submit to two jurisdiction of governmental control: the External Control, represented by the National Congress with the assistance of the Tribunal de Contas da União (TCU) [General Accounting Office] and the Internal Control, executed by the Sistema de Controle Interno do Poder Executivo Federal (System of Internal Control and Federal Executive Power) and units of internal auditing, attached in the structure of the agency. For the accomplishment of its activities the control agencies has specific methods and tools, among which the audit technique is emphasized, accomplished by two fields of work: (1) Regularity auditing focused on the legality of the management acts; and (2) Operational auditing, that evaluates the public management performance regarding its economicity, efficiency and effectiveness. The use of performance indicators is substantial for the realization of audits of operational nature. The TCU brings forward the methodology of Balanced Scorecard (BSC) as a tool able to assist the development of a matrix of indicators that contemplate both financial measures, and aspects of operational performance. Giving the background, the present study aimed the development of an operational audit framework grounded on BSC methodology, Able to help the accomplishment of audits of operational nature in the ambit of IFES. To achieve the goal of the search, at first a bibliographic review of the subject was carried out in order to establish a relationship between BSC and operational auditing. Once it was verified the possibility of adaptation from BSC to operational auditing, the next step was identifying the scene of operational auditing in the ambit of the Instituições Federais de Ensino Superior (Federal Institute of higher education), using as a tool of data acquisition the online interview with auditors from IFES. Subsequently, through documentary search it was identified the procedures for rating the dimensions of the performance in the operational auditing process realized by Tribunal de contas da união (General Accounting Office). The data gained from the interview and documentary search of operational auditing reports from TCU were analyzed by the content analyzes technique, allowing the development of operational auditing framework grounded on the BSC methodology. The framework validation was given through the development of an operational auditing work by the audits from one Instituição Federal de Ensino Superior (Federal Institute of higher education). Lastly, an interview with the audit team boss was made in order to verify his perception over the developed framework. The framework developed consist in the graphic representation of the major program elements and governmental activity to be analyzed in an operational auditing work in one of the four dimensions of performance, as well as the relations of cause and effect of such elements. Therefore, the framework helps to identify the causes and consequences of the possible findings of the auditing and the results expected with implementation of the audit’s advice. Thereby, the search reassert the BSC adaptability to different organizational goals, mainly by the fact that the present study not focusing in the translation of strategy, but on another analyze go al, that is, the building of a rating system of the government acting performance.